Identifikasi Kekeliruan Penggunaan Metode Statistika pada Artikel yang Dimuat di Jurnal OJS Unud - Ni Luh Putu Suciptawati (Jurnal Matematika, 2019)
Abstract: The statistical method plays a role in scientific research. Use of appropriate statistical methods in analyzing data influences research conclusions. Misuse statistical methods will lead to incorrect conclusions. This study aims to identify the misuse of statistical methods in articles published in the OJS UNUD Journals. We reviewed 97 articles from OJS UNUD Journals published in 2017. This study found several misuse statistical methods these included: misuse multiple linear regression analysis, generalize conclusions based on descriptive statistics, inappropriate use of ANOVA, misinterpretation of negative correlation values, use of Chi square test for small samples, use of t-test two samples for observations with ordinal scale Keywords: statistical methods, misuse statistical, OJS UNUD Journal